2003
DOI: 10.3346/jkms.2003.18.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Placenta Growth Factors and Their Receptors In the Normal and Pregnancy-Induced Hypertensive Human Placentas

Abstract: Placental development requires extensive angiogenesis and the invasion of the maternal decidua by the trophoblasts. Adequate and organized interaction of vascular endothelial growth factors (VEGF), placenta growth factors (PlGF), and their receptors are essential for a normal development and function of the placenta. In this study, we evaluated the expressions of PlGFs and their receptors, mRNAs by Northern blotting, in situ hybridization and RT-PCR in the normal and pregnancy-induced hypertensive (PIH) placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The PlGF levels in the peripheral blood of pre‐eclamptic women are lower than those in normal pregnant women . A decrease in PlGF mRNA expression has been reported in pre‐eclampsia placenta . This study confirmed that PlGF mRNA expression in pre‐eclampsia placenta was lower than that in normal pregnancy placenta.…”
Section: Discussionsupporting
confidence: 81%
“…The PlGF levels in the peripheral blood of pre‐eclamptic women are lower than those in normal pregnant women . A decrease in PlGF mRNA expression has been reported in pre‐eclampsia placenta . This study confirmed that PlGF mRNA expression in pre‐eclampsia placenta was lower than that in normal pregnancy placenta.…”
Section: Discussionsupporting
confidence: 81%
“…This heterodimer has weaker mitogenic activity, and its formation leads to depletion of VEGF homodimer levels and, consequently, of its angiogenic activity. [25][26][27] In addition, VEGF/PlGF induces the formation of sFlt-1. [28][29][30] Through these mechanisms, the VEGF/PlGF heterodimer contributes to the antiangiogenic state and consequent decrease in VEGF found in BPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, Smith et al (1999) concluded that reactive oxygen and nitrogen are not induced by TNF␣ and IFN␥ and do not mediate cytokine-induced apoptosis in this setting. Vascular endothelial growth factor (VEGF)-A and placental growth factor (PlGF) and their receptors are generally accepted to be required for healthy placental development, and alteration of PlGF-2 (lower) and PlGFR-1 (raised) mRNA expressions in the placenta are related to the pathogenesis of pregnancy-induced hypertension (Cho et al, 2003). Tsatsaris et al (2003) suggest two mechanisms of pre-eclamptic disease: 1) Overproduction of competitive soluble VEGFR-1 that leads to suppression of (VEGF)-A and PlGF mediated effects; and 2) Lowered membrane-bound (VEGFR-1) in the placental bed that results in defective uteroplacental development.…”
Section: Cell Pathology Of Pre-eclampsiamentioning
confidence: 99%